Glycans in Trained Immunity: Educators of innate immune memory in homeostasis and disease - Almeida, P (2024)
Trained Immunity is defined as a biological process normally induced by exogenous or endogenous insults that triggers epigenetic and metabolic reprogramming events associated with long-term adaptation of innate immune cells. This trained phenotype confers enhanced responsiveness to subsequent triggers, resulting in an innate immune "memory" effect. Trained Immunity, in the past decade, has revealed important benefits for host defense and homeostasis, but can also induce potentially harmful outcomes associated with chronic inflammatory disorders or autoimmune diseases. Interestingly, evidence suggest that the "trainers" prompting trained immunity are frequently glycans structures. In fact, the exposure of different types of glycans at the surface of pathogens is a key driver of the training phenotype, leading to the reprogramming of innate immune cells through the recognition of those glycan-triggers by a variety of glycan-binding proteins (GBPs) expressed by the immune cells. β-glucan or mannose-enriched structures in Candida albicans are some of the examples that highlight the potential of glycans in trained immunity, both in homeostasis and in disease. In this review, we will discuss the relevance of glycans exposed by pathogens in establishing key immunological hubs with glycan-recognizing receptors expressed in immune cells, highlighting how this glycan-GBP network can impact trained immunity. Finally, we discuss the power of glycans and GBPs as potential targets in trained immunity, envisioning potential therapeutic applications.